THE IMPLEMENTATION OF AUDIO-LINGUAL METHOD IN TEACHING PRONUNCIATION: A CASE STUDY AT MAN 2 KOTA PEKANBARU - Farhana, Nur; Amelia, Rizki (Journal of English and Arabic Language Teaching, 2025)
This research discussed about teaching and learning English by using Audio-Lingual Method. Therefore, this research aimed to know the implementation of applying audio-lingual method in teaching pronunciation at MAN 2 Kota Pekanbaru. This research used a qualitative case study as the research design. The data collected from two English teachers at MAN 2 Kota Pekanbaru who used Audio-Lingual method. The data of this study took from the interview and the results show that both of teachers have positive responses toward the implementation of Audio Lingual Method. The researcher concluded that the Audio-Lingual Method is well implemented and does have positive impact towards students’ pronunciation.